Care of the self in the daily living of nurses: an integrative review - Edson José da Silva Júnior; Alexandre Pazetto Balsanelli; Vanessa Ribeiro Neves
ABSTRACT Objectives: to identify if nurses care for themselves and describe such practices. Methods: this is an integrative review of the literature published between 2006 and 2018 and indexed in the Literatura Latino-Americana e do Caribe em Ciências da Saúde, Medical Literature Analysis and Retrieval System Online and Web of Science databases. Results: the sample totaled 20 articles, grouped by content similarity in the thematic categories "limits and possibilities for the care of the self", "knowledge about practices on the care of the self" and "implications of care of the self in professional practice". Final considerations: the knowledge about techniques on caring for the self allows nurses to develop themselves personally and professionally. We suggest to managers and administrators a redirection of the nursing practice that contemplates the strengthening of the nurse as the manager of care and leader of the team, as well as the inclusion of the concept of care of the self in the curricula of undergraduate and graduate nursing courses.